2020
DOI: 10.2320/matertrans.mt-mn2019039
|View full text |Cite
|
Sign up to set email alerts
|

Cu<sub>2</sub>O Nanoparticles: A Simple Synthesis, Characterization and Its Photocatalytic Performance toward Methylene Blue

Abstract: Cuprous oxide nanoparticles (Cu 2 O-NPs) were fabricated by a simple solution-phase reduction route with a one-step reduction method. The used original chemicals were the copper sulfate and the sodium sulfite. The physicochemical properties of Cu 2 O-NPs were investigated by different methods such as XRD, Raman, SEM, and UV-Vis spectra. The results show that the molar ratio of precursors ([CuSO 4 ]/[Na 2 SO 3 ]) not only affects crystal structure and morphology but also affects the crystallinity of crystals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These electrons oxidize organic pollutants 15,16) by producing free hydroxyl radicals (•OH) at higher concentration and faster by using UV light. 17) Photocatalyst materials have been used for environmental treatment 18,19) and, over recent decades, several inorganic semiconductors have been studied due to their high oxidative performance without requiring chemicals or high temperatures. 20) They have been used in photovoltaic and photodegradation of organic pollutants in air and water.…”
Section: Introductionmentioning
confidence: 99%
“…These electrons oxidize organic pollutants 15,16) by producing free hydroxyl radicals (•OH) at higher concentration and faster by using UV light. 17) Photocatalyst materials have been used for environmental treatment 18,19) and, over recent decades, several inorganic semiconductors have been studied due to their high oxidative performance without requiring chemicals or high temperatures. 20) They have been used in photovoltaic and photodegradation of organic pollutants in air and water.…”
Section: Introductionmentioning
confidence: 99%
“… 50 Furthermore, Raman signals observed at 215, 500, and 640 cm −1 are associated with the second-order overtone mode 2Eu, Raman-allowed mode F 2g and Raman-allowed mode TO, respectively, for Cu 2 O. 51 …”
Section: Resultsmentioning
confidence: 98%
“…50 Furthermore, Raman signals observed at 215, 500, and 640 cm −1 are associated with the second-order overtone mode 2Eu, Raman-allowed mode F 2g and Raman-allowed mode TO, respectively, for Cu 2 O. 51 The optical properties of the synthesized CuNPs were analyzed using UV-visible and CD spectroscopy. The UV-visible spectra showed typical features in the region corresponding to the LSPR and interband transition of CuNPs: a broad absorption peak covering 500-800 nm with a shoulder at around 620 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Raw materials for the production of Cu2O are available in nature. The Cu2O fabricated processes are relatively simple and inexpensive [1][2][3][4][5][6][7]. Therefore, Cu2O is one of the fascinating semiconductor materials that is attracting attention in production and application research in many areas such as biosensors, gas sensors, lithium-ion batteries, optoelectronics, luminescence, photocatalysts for air purification, water purification by solar energy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Cu2O is one of the fascinating semiconductor materials that is attracting attention in production and application research in many areas such as biosensors, gas sensors, lithium-ion batteries, optoelectronics, luminescence, photocatalysts for air purification, water purification by solar energy, etc. [4][5][6][7][8][9][10][11][12]. Research works have reported that Cu2O semiconductor nanomaterials in particular as well as semiconductor nanomaterials in general (ZnO, TiO2, etc.)…”
Section: Introductionmentioning
confidence: 99%